Perinatal outcomes in women with class IV obesity compared to women in the normal or overweight body mass index categories: A population‐based cohort study in Qatar - Fathima Minisha (16475100) (2023)
Background The prevalence of childhood and adult obesity is rising exponentially worldwide. Class IV obesity (body mass index, BMI ≥50 kg/m2) is associated with a higher risk of adverse perinatal outcomes. This study compared these outcomes between women with class IV obesity and women in the normal or overweight categories during pregnancy. Methods A retrospective cohort study was performed in Qatar, including women having singleton live births beyond 24 weeks of gestation, classified into two class IV obesity and normal/overweight (BMI between 18.5 and 30.0 kg/m2). The outcome measures included the mode of delivery, development of gestational diabetes and hypertension, fetal macrosomia, small for date baby, preterm birth and neonatal morbidity. Adjusted odds ratios (aOR) with 95% confidence intervals (95% CI) were determined using multivariable logistic regression models. Results A total of 247 women with class IV obesity were compared with 6797 normal/overweight women. Adjusted analysis showed that women with class IV obesity had 3.2 times higher odds of cesarean delivery (aOR: 3.19, CI: 2.26–4.50), 3.4 times higher odds of gestational diabetes (aOR: 3.39, CI: 2.55–4.50), 4.2 times higher odds of gestational hypertension (aOR: 4.18, CI: 2.45–7.13) and neonatal morbidity (aOR: 4.27, CI: 3.01–6.05), and 6.5 times higher odds of macrosomia (aOR 6.48, CI 4.22–9.99). Conclusions Class IV obesity is associated with more adverse perinatal outcomes compared with the normal or overweight BMI categories. The study results emphasized the need for specialized antenatal obesity clinics to address the associated risks and reduce complications. Other Information Published in: Obesity Science & Practice License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/osp4.698